LEGAL PROTECTION FOR SOCIAL SECURITY ADMINISTERING BODY HEALTH PARTICIPANTS - Irayadi, Muhamad (Awang Long Law Review, 2024)
In order to legally protect the rights of patients participating in the Social Security Administering Body (BPJS) of Health in obtaining health services, the government issued Law Number 24 of 2011, which stipulates that two state-owned enterprises, namely PT Askes (Persero) and PT Jamsostek (Persero) were transformed into public service agencies to implement five programs mandated by Law Number 40 of 2004, namely the health insurance program for BPJS Health and other programs are handed over to BPJS Employment. This study aims to analyze how to protect BPJS Health participants. This study uses a normative legal research method with field data as a complement. The results of the study Legal protection for BPJS Health participants who are hospitalized in hospitals from the regulatory aspect have protected their rights both as consumers of services, as hospital patients and as BPJS Health participants. The method of resolving BPJS Health service disputes through mediation reflects the importance of a consensual approach to dispute resolution. Mediation is chosen for several theoretical reasons, such as the dominance of a culture that prioritizes harmony and togetherness, and the balance of power between the disputing parties.